2018
DOI: 10.14740/cr735w
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tp-Te/QT Ratio With Ventricular Tachycardia in Patients With Idiopathic Outflow Tract Ventricular Premature Contraction

Abstract: BackgroundIdiopathic outflow tract ventricular premature contraction (VPC) can evolve into ventricular tachycardia (VT) via triggered activity mechanism. Transmural dispersion of repolarization (TDR) might play a role in idiopathic outflow tract VT by inducing phase 2 early afterdepolarization (EAD) and serve as the functional substrate for VT. Tp-Te/QT ratio as an arrhythmogenesis index has been reported to be associated with the incidence of ventricular arrhythmia. This study aims to investigate the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition, it is thought that MP may cause malignant arrhythmias and sudden death, similar to some studies conducted with smoking. Changes in the distribution of transmural repolarization may play a role in this process [ 16 ]. This study aimed to show the relationship between MP use and new ventricular repolarization parameters and EFT, which have not been reported before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is thought that MP may cause malignant arrhythmias and sudden death, similar to some studies conducted with smoking. Changes in the distribution of transmural repolarization may play a role in this process [ 16 ]. This study aimed to show the relationship between MP use and new ventricular repolarization parameters and EFT, which have not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…This interval is called the Tp-e interval. Prolongation of the Tp-e interval has been associated with ventricular arrhythmias and increased sudden cardiac death [ 16 ]. In this study, the Tp-e interval was higher in the MP group.…”
Section: Discussionmentioning
confidence: 99%
“…QRS-T angle is defined as the angle between the QRS axis and T-wave axis 13 , 14 . Widened QRS-T angle predicts abnormal depolarization and repolarization, in situations with abnormal electrical activation including ischemia, bundle branch block, and left ventricular hypertrophy 21 . There is a limitation in the use of spatial QRS-T angle in clinical practice as a result of difficulties in the calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the interval from the peak to the end of T wave (T peak-Tend interval [Tp-e]) has been proposed for use in the prediction of malignant arrhythmia in SCD [10] [11] [12] [13]. Previous canine and rabbit left ventricular wedge models have indicated that the Tp-e interval in an electrogram was measured across the wedge correlates well with the transmural dispersion of cellular repolarization (TDR) [14].…”
Section: Introductionmentioning
confidence: 99%